PENGARUSUTAMAAN MODAL SOSIAL DALAM PEMBANGUNAN PERDESAAN - Abdul Rahman; Nurlela Nurlela; Rifal Rifal (Madani Jurnal Politik dan Sosial Kemasyarakatan, 2020)
This article discusses the importance of social capital in rural development. Social capital is deemed necessary in rural development activities because historical data shows that development carried out by the government of the Republic of Indonesia, especially during the New Order administration tended to neglect community participation, even though it was the community who would utilize the development results. Entering the era of reform, the direction of rural development underwent a paradigm shift, in which the community is no longer placed as an object, but has been positioned as the subject of development, which is more popularly known as development with the botton up approach. The paradigm is then elaborated on empirical reality by placing Tompobulu Village community as a locus of research. The results showed that the development activities in this village could run in accordance with expectations because they got the support of the community who synergized with the government, and placed social capital as the basic capital in implementing development.